A report of natural remanent magnetization of dirt ice layers collected from Allan Hills, Southern Victoria Land, Antarctica - Funaki, Minoru; Nagata, Takesi (1985)
P(論文) Paleomagnetic studies are performed for the dirt ice specimens collected from the Allan Hills, Southern Victoria Land, Antarctica. These specimens have fairly stable NRM against AF demagnetization up to 500 Oe. Every specimen has normal magnetization with 2.5×(10)^<-6> emu・g^<-1> intensity, -69°inclination and 164°declination. The NRM carriers are estimated to be almost pure magnetite with a pseudosingle domain structure. Although the NRM acquisition mechanism cannot be explained at this time, it may be important to evaluate the possibility of NRM acquisition when the snow containing volcanic ash changes to ice under pressure. Since the nondipole components of the geomagnetic field are large in the southern polar cap area, the NRM cannot estimate the age and the place of NRM aquisition from the VGP position of these specimens. departmental bulletin paper